The prevalence of enamel and dentine caries lesions and their determinant factors among children living in fluoridated and non-fluoridated areas - Mohd Nor, Nor Azlida; Chadwick, Barbara Lesley; Farnell, Damian J.J.; Chestnutt, Ivor Gordon (Dennis Barber, 2019)
Objective: To determine the prevalence and severity of dental caries (at dentine and enamel levels of diagnosis) amongst Malaysian children and to investigate determinant factors associated with caries detection at these different thresholds. Methods: This study involved life-long residents aged 12 years-old in fluoridated and non-fluoridated areas in Malaysia (n=595). The survey was carried out in 16 public schools by a calibrated examiner, using ICDAS-II criteria. A questionnaire on socio-demographic and oral hygiene practices was self-administered by parents/guardians. Data were analysed using Mann-Whitney U tests and logistic regression. Results: The overall response rate was 74.4%. Caries prevalence at the dentine level or at the dentine and enamel level was significantly (p<0.001) higher among children in the non-fluoridated area (D1-6 MFT>0 = 82.4%, D4-6 MFT>0 = 53.5%) than in the fluoridated area (D1-6 MFT>0 = 68.7%, D4-6 MFT>0 = 25.5%). Considering only the decayed component of the index, no significant differences were observed between the two areas when the detection threshold was set at enamel caries (D1-3) (p=0.506). However, when the detection criteria were elevated to the level of caries into dentine (D4-6) there were clear differences between the fluoridated and non-fluoridated areas (p=0.006). Exposure to fluoridated water proved a significant predictor for lower caries prevalence in the statistical model. Children whose father and mother had a low monthly income had a significantly higher dentine caries prevalence. Conclusion: Results confirmed existing evidence of the benefit of water fluoridation in caries prevention. Detection criteria set at caries into dentine shows clear differences between fluoridated and non-fluoridated areas. Exposure to fluoridated water and socio-economic status were associated with caries prevalence. © BASCD 2019.